An example of multilingual language use: Ukrainian and Russian loanwords in the Transcarpathian variety of the Hungarian language in Ukraine - Váradi, Krisztián (Cahiers de l’ILOB / OLBI Journal, 2025)
This article considers the peculiarities of the language use of Transcarpathian Hungarian students, with a focus on the knowledge of the meanings of Ukrainian and Russian loanwords. In this research, a total of 63 students from local colleges, universities and vocational schools solved five different tasks during an online survey. They were asked to describe pictures in Hungarian, to replace Ukrainian and Russian borrowings with Hungarian standard equivalents, to solve multiple choice questions on the meaning of loanwords, to name concepts based on definitions, and to list additional loanwords from their everyday language use. The results show that the majority of the Transcarpathian Hungarian students are familiar with the meanings of Slavic lexical borrowings; however, they prefer the Hungarian language equivalents due to their mother tongue dominance. The only exceptions are culture-specific terms (xenisms), including the names of currencies, institutions, and food.